6
$\begingroup$

I have the following recurrence relation and boundary condition? $$ f(n,m) = \frac{\alpha n}{n+m} f(n-1,m) + \frac{\beta m}{n+m} f(n,m-1) + 1 $$

$$ f(n,0) = \frac{1-\alpha^{n+1}}{1-\alpha}, f(0,m) = \frac{1-\beta^{m+1}}{1-\beta} $$ Is it possible to get a exact solution for this recurrence relation?

$\endgroup$
1
  • 1
    $\begingroup$ I have tried to use the generating function method but I failed. $\endgroup$
    – Lili Si
    Commented May 3, 2023 at 7:21

1 Answer 1

4
$\begingroup$

Let $$g(n,m)=\sum\limits_{i=0}^{n}\sum\limits_{j=0}^{m}\binom{i+j}{j}\binom{n-i+m-j}{m-j}\alpha^i\beta^j$$ I conjecture that $$g(n,m)=\binom{n+m}{m}f(n,m)$$ Here is the PARI prog to verify this conjecture:

f(n, m) = if(n==0 || m==0, (m==0)*(1 - a^(n+1))/(1-a)+(n==0)*(1 - b^(m+1))/(1-b)-(n==0 && m==0), a*n/(n+m)*f(n-1, m)+b*m/(n+m)*f(n, m-1)+1)
g(n, m) = sum(i=0, n, sum(j=0, m, binomial(i+j,j)*binomial(n-i+m-j,m-j)*a^i*b^j))
test(n, m) = g(n, m)==binomial(n+m, m)*f(n, m)
n=6; x=sum(i=0, n, sum(j=0, n, test(i, j)))

Here is the proof of a user with the nickname svv on a scientific forum dxdy.ru (here is the link to the topic):

Let $$g(n,m)=\binom{n+m}{m}f(n,m)$$ Then we have $$g(n,m)=\alpha\,g(n-1,m)+\beta\,g(n,m-1)+\binom{n+m}{m}$$ If we make a little change $$g(n,m)=[n\geqslant 0]\cdot[m\geqslant 0]\cdot\left(\alpha\,g(n-1,m)+\beta\,g(n,m-1)+\binom{n+m}{m}\right)$$ where square brackets denote Iverson brackets, then the basic conditions given for $f(n,0)$ and $f(0,m)$ holds.

From the recurrence relation and $g(0,0)=1$ it follows that $g(n,m)$ as a polynomial of $\alpha,\beta$ for $n,m\geqslant 0$ has degree $n$ by $\alpha$ and degree $m$ by $\beta$: $$g(n,m)=\sum\limits_{i=0}^n \sum\limits_{j=0}^m c_{n,m}^{i,j} \alpha^i \beta^j$$

Substitute this into a recurrence relation and equate the coefficients at the same degrees of $\alpha$ and $\beta$. Then we have $$c_{n,m}^{i,j}=\begin{cases}\binom{n+m}{m}&\text{if}\;i=j=0\\c_{n-1,m}^{i-1,j}+c_{n,m-1}^{i,j-1}&\text{otherwise}\end{cases}$$

Note that the differences between the first lower and first upper indices are the same in all terms: $n-i=(n-1)-(i-1)$. Similarly, the differences between the second lower and second upper indices are the same. This suggests using (maybe temporarily) other coefficients, more invariant, so to speak, instead of $c$: $$d_{p,q}^{i,j}=c_{p+i,q+j}^{i,j},\quad c_{n,m}^{i,j}=d_{n-i,m-j}^{i,j}$$

Then we have $$d_{p,q}^{i,j}=\begin{cases}\binom{p+q}{q}&\text{if}\;i=j=0\\d_{p,q}^{i-1,j}+d_{p,q}^{i,j-1}&\text{otherwise}\end{cases}$$

If the conditions had the form $$d_{p,q}^{i,j}=\begin{cases}1&\text{if}\;i=j=0\\d_{p,q}^{i-1,j}+d_{p,q}^{i,j-1}&\text{otherwise}\end{cases}$$ then the solution would be $$d_{p,q}^{i,j}=\binom{i+j}{j}$$ For the proof, see this answer.

Due to the linearity of the recurrence relation, if now $d_{p,q}^{0,0}$ is multiplied by the coefficient $\binom{p+q}{q}$, that is, take $d_{p,q}^{0,0}=\binom{p+q}{q}$, all other $d_{p,q}^{i,j}$ will be multiplied by the same coefficient, so we get $$d_{p,q}^{i,j}=\binom{i+j}{j}\binom{p+q}{q}$$ Returning to $c_{n,m}^{i,j}$, we get the explicit form $$c_{n,m}^{i,j}=\binom{i+j}{j}\binom{n-i+m-j}{m-j}$$ and the desired formula.

$\endgroup$
4
  • 2
    $\begingroup$ The obvious way to prove it would be to show that the identity holds at the boundary conditions and is preserved by the recurrence. Since the terms can be grouped trivially by the exponents of $\alpha$ and $\beta$ this should be easy. $\endgroup$ Commented May 3, 2023 at 8:46
  • 3
    $\begingroup$ @PeterTaylor, thak you for comment! Could you write your own answer including the proof? In that case, I could delete my useless answer based on the experimental result. $\endgroup$ Commented May 3, 2023 at 8:51
  • 3
    $\begingroup$ @Notamathematician Your answer is not "useless" as you guessed the correct form. Note that writing the OP in terms of $g(n,m)=\binom{n+m}{m}f(n,m)$ results in a simpler recursion ($\frac{\alpha n}{n+m}$ replaced with $\alpha$, and the other factor with $\beta$) which should also allow for a generating function proof. $\endgroup$ Commented May 3, 2023 at 21:16
  • 1
    $\begingroup$ A closed expression for $g(n,m)$: $$g(n,m) = (n+m+1)\binom{n+m}n \int_0^1 (1+(\alpha-1)t)^n (1+(\beta-1)t)^m {\rm d}t,$$ $\endgroup$ Commented May 10, 2023 at 2:01

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .